Flavonoids Extracted from Asteriscus graveolens Improve Glucose Metabolism and Lipid Profile in Diabetic Rats - El-ouady, Fadwa; Bachir, Fatima; Eddouks, Mohamed (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2021)
Aims: This study aimed to evaluate the antidiabetic and antihyperlipidemic effects of Asteriscus graveolens. Background: Asteriscus graveolens (Asteraceae) is a medicinal plant widely used by the Moroccan population to treat various diseases, including diabetes. Objective: This work aimed to assess the capacity of flavonoids extracted from Asteriscus graveolens (FEE) to improve diabetes mellitus and dyslipidemia in normal and STZ-induced diabetic rats. Methods: Flavonoids were extracted from A. graveolens using the Soxhlet apparatus and using different organic solvents. Normal and streptozotocin-induced diabetic rats were treated orally by the extract of A. graveolens at a dose of 10 mg/kg. The oral treatment during 15 days was used to evaluate the effect of the flavonoids extracted from A. graveolens on blood glucose level and lipid profile in normal and diabetic rats. The oral glucose tolerance test, as well as the analysis of the histopathological examination of the liver, was performed. The antioxidant activity of FEE was also assessed by the method of trapping of free radical 2,2-diphenyl-1 picrylhydrazyl (DPPH), in order to estimate the mechanisms of action involved by FEE to improve hyperglycemia and lipid profile in normal and diabetic rats. Results: FEE reduced serum glucose concentrations in both normal and diabetic rats and exhibited lowering total cholesterol and triglycerides effects as well as improvement of the HDL-cholesterol serum level in the last group. In addition, a remarkable influence on glucose tolerance was also noticed after FEE treatment. Moreover, FEE was able to improve the histopathological status of the liver and was found to possess a potent antioxidant effect in vitro. Conclusion: In conclusion, this study demonstrates the hypoglycemic and antihyperlipidemic effects of FEE in rats and supports its traditional use for the management of diabetes.
Keywords: Asteriscus graveolens